Spatial distribution of the human development index, HIV infection and AIDS-Tuberculosis comorbidity: Brazil, 1982 - 2007 - Antonio Luiz Rodrigues-Júnior; Antonio Ruffino-Netto; Euclides Ayres de Castilho (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: AIDS epidemic has given visibility to the incidence of tuberculosis, for being the most frequent opportunistic infection. It is known that individuals who are socially vulnerable are more susceptible to HIV transmission and tuberculosis as well. OBJECTIVE: This study aims to conduct a geoepidemiological study on HIV/AIDS, AIDS-Tuberculosis co-infection and social vulnerability. METHOD: This is an ecological study using incidence rates and the human development index to produce thematic maps and a descriptive analysis of epidemiology. The records of reported cases of HIV/AIDS from 1982 to 2007 were used, considering as cases of AIDS-Tuberculosis those records that were positively diagnosed with tuberculosis and those records with unknown diagnosis of tuberculosis, but showing compatible signs and symptoms with tuberculosis (fever, cough, cachexia and asthenia). RESULTS: The maps allowed the identification of areas with social differences and different patterns of incidence of HIV/AIDS and AIDS-Tuberculosis; regional differences were similar to those found by Josué de Castro, in 1940; regions with higher human development index values also showed higher incidence HIV/AIDS and AIDS-Tuberculosis. CONCLUSION: The prevention of HIV infection must be geographically specific, given socioeconomic and cultural differences. Although official records show decline in AIDS-TB co-infection, treatment of cases of HIV/AIDS should observe the occurrence of opportunistic diseases, which should be notified and/or updated.